2018
DOI: 10.1016/j.ensci.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic state of periictal hyperperfusion revealed by arterial spin-labeling perfusion MR images with dual postlabeling delay

Abstract: BackgroundMagnetic resonance imaging (MRI), including perfusion MRI with arterial spin labeling (ASL) and diffusion-weighted imaging (DWI), are applied in the periictal detection of circulatory and metabolic consequences associated with epilepsy. Although previous report revealed that prolonged ictal hyperperfusion on ASL can be firstly detected and cortical hyperintensity of cytotoxic edema on DWI secondarily obtained from an epileptically activated cortex, the hemodynamic state of the periictal hyperperfusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 29 publications
(119 reference statements)
4
36
1
Order By: Relevance
“…If this still give equivocal results, an ictal SPECT can be performed to help to identify the epileptic zone by showing hyperperfusion. In the peri-ictal stage, perfusion MRI with arterial spin labelling (ASL) is also showing great promise in the identification of regional hyperperfusion secondary to the increased metabolic demands ( Takahara et al , 2018 ).…”
Section: How To Study Malformations Of Cortical Developmentmentioning
confidence: 99%
“…If this still give equivocal results, an ictal SPECT can be performed to help to identify the epileptic zone by showing hyperperfusion. In the peri-ictal stage, perfusion MRI with arterial spin labelling (ASL) is also showing great promise in the identification of regional hyperperfusion secondary to the increased metabolic demands ( Takahara et al , 2018 ).…”
Section: How To Study Malformations Of Cortical Developmentmentioning
confidence: 99%
“…These ictal MRI findings on ASL and DWI are reversible in most cases. 65,67 Takahara et al reported that ASL hyperperfusion is superior to DWI in the periictal detection of epileptic events. 67
Figure 9.Ictal state seizure with Todd’s paralysis.
…”
Section: Asl Versus Dsc Perfusion Imagingmentioning
confidence: 99%
“…65,67 Takahara et al reported that ASL hyperperfusion is superior to DWI in the periictal detection of epileptic events. 67
Figure 9.Ictal state seizure with Todd’s paralysis. 56-year-old male with seizure and focal right arm weakness and aphasia.
…”
Section: Asl Versus Dsc Perfusion Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial use of brain magnetic resonance imaging is useful not only to detect cerebrovascular disorders and other neurological conditions but also to evaluate seizure foci and spread of seizures via neural network. Hyperintensity of diffusionweighted imaging especially in the cortex and hyperperfusion of arterial spin labeling can help early diagnosis of nonconvulsive status epilepticus [118,119,121,122].…”
Section: Brain Imagingmentioning
confidence: 99%